Single clips versus multi-firing clip device for closure of mucosal incisions after peroral endoscopic myotomy (POEM) - Verlaan, Tessa; Ponds, Fraukje A. M.; Bastiaansen, Barbara A. J.; Bredenoord, Albert J.; Fockens, Paul (Endoscopy International Open, 2016)
Background and aims: After Peroral Endoscopic Myotomy (POEM), the mucosal incision is closed with endoscopically applied clips. After each clip placement, a subsequent clipping device has to be introduced through the working channel. With the Clipmaster3, three consecutive clips can be placed without reloading which could reduce closure time. We performed a prospective study evaluating efficacy, safety, and ease of use. Closure using Clipmaster3 was compared to closure with standard clips.Methods: Patients undergoing closure with the Clipmaster3 were compared to patients who underwent POEM with standard clip closure.Results: In total, 12 consecutive POEM closures with Clipmaster3 were compared to 24 standard POEM procedures. The Clipmaster3 and the standard group did not differ in sex distribution, age (42 years [29 – 49] vs 41 years [34 – 54] P = 0.379), achalasia subtype, disease duration, length of the mucosal incision (25.0 mm [20 – 30] vs 20.0 mm [20 – 30], P = 1.0), and closure time (622 seconds [438 – 909] vs 599 seconds [488 – 664] P = 0.72). Endoscopically successful closure could be performed in all patients. The proportion of all clips used that were either displaced or discarded was larger for Clipmaster3 (8.8 %) compared to standard closure (2.0 %, P  = 0.00782). Ease of handling VAS (visual analogue scale) score for Clipmaster3 did not differ between endoscopist and endoscopy nurse (7 out of 10).Conclusions: Clipmaster3 is feasible and safe for closure of mucosal incisions after POEM. Clipmaster3 was not associated with reduced closure time. Compared to standard closure, more Clipmaster3 clips were displaced or discarded to achieve successful closure. A training effect cannot be excluded as a cause of these results.Study registration: NCT01405417